Dynamic UCLA for aesthetic rehabilitation on implant in a patient with special needs: A 4-year follow-up case report (Research, Society and Development, 2020)
This study aims to present the dynamic UCLA as a prosthetic option to restore a tilted implant, replacing a missing maxillary left lateral incisor with a functional and aesthetic screw-retained crown. Dental implants show high success rates; however, complications related to three-dimensional positioning of the implant are common. The correction of the implant position usually requires machined angled abutments or complex surgical procedures, which results in long and difficult treatment, and increases the treatment final cost. A 45-years-old male patient sought for specialized dental care to restore the front missing tooth esthetic area. The patient has limited mouth opening, mental and physical disabilities, so the construction of a metal-ceramic prosthesis with the aid of dynamic UCLA was proposed as a straightforward and low-cost procedure under the sign of free and informed consent. The prosthetic treatment provided aesthetic results and patient satisfaction without complications after a four-year follow-up.